1997
DOI: 10.1002/(sici)1097-4628(19970124)63:4<439::aid-app5>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinker reactivity and the structure of superabsorbent gels

Abstract: A 13 C-labeled crosslinker (trimethylolpropane triacrylate, TMPTA) was synthesized and copolymerized with acrylic acid while monitoring the relative rates of reaction of the crosslinker and acrylic acid by 13 C-NMR. This allowed easy quantification of the concentration of the minor component (crosslinker) in the polymer and monomer mixture to levels as low as 0.02%. Polymerizations were conducted in 5 mm NMR tubes under varied temperature, percent neutralization (pH), and percent solids. Reactivity ratios were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…Possibility of probe coating during the synthesis process and the low crosslinker content associated to hydrogels production are factors affecting negatively the use of such technique in this context. Use of off‐line FTIR analysis of isolated polymers, chemical analysis of pendant double bonds or 13C labelling of the crosslinker should provide improved information concerning the crosslinking process. Conversely, the use of multiple detection (especially including light scattering) in SEC analysis proved to be very important in order to obtain a rigorous characterization of products molecular architecture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Possibility of probe coating during the synthesis process and the low crosslinker content associated to hydrogels production are factors affecting negatively the use of such technique in this context. Use of off‐line FTIR analysis of isolated polymers, chemical analysis of pendant double bonds or 13C labelling of the crosslinker should provide improved information concerning the crosslinking process. Conversely, the use of multiple detection (especially including light scattering) in SEC analysis proved to be very important in order to obtain a rigorous characterization of products molecular architecture.…”
Section: Resultsmentioning
confidence: 99%
“…Crosslinker amount used in hydrogels preparation is very low (a few percent) and even with off‐line FTIR monitoring the study of the crosslinking process is a difficult task. 13C labelling of the crosslinker (as before performed with trimethylolpropane triacrylate (TMPTA) in the framework of network formation in superabsorbent gels) should be a better option in this context.…”
Section: Methodsmentioning
confidence: 99%
“…As previously pointed out by Arriola et al, 27 the temperature had little influence because the activation energy was low for radical propagation reactions. Network formation follows several elementary reactions 27 involving the copolymerization between AA and MBA C . The Flory-Stockmayer 28,29 theory is widely used to predict the gel network buildup of a crosslinking polymerization system.…”
Section: Ph Influencementioning
confidence: 99%
“…AEPEG is less reactive than acrylate crosslinkers and it produced a network that has lower crosslinking density during the initial stage of polymerization and is apparently more uniform in crosslinking density as opposed to AEPEG of 3400 molecular weight; moreover, the mechanism of polymerization of allyl crosslinkers is normal vinyl polymerization. Arriola et al22 found that the relative rate of incorporation of trimethylol propane triacrylate (TMPTA) crosslinker into polyacrylic acid gels was exceedingly rapid; further, all of the double bonds of TMPTA were incorporated into the gel network, and superabsorbents prepared with TMPTA consisted of (1) a very heterogeneous network of highly crosslinked, high molecular weight polyacrylic acid formed during the early phase of the polymerization; (2) chains of low molecular weight that formed in the middle of the polymerization bridging through the pendant vinyl groups and containing a greater distance between crosslinking sites than chains formed initially; and (3) grafted polymer formed especially toward the end of the polymerization. However, the low efficiency (∼ 60–70%) of TMPTA is postulated to be caused by a solubility problem in the monomer mixture at high neutralization, steric hindrance, and a lower percentage of solids.…”
Section: Introductionmentioning
confidence: 99%